Pelatihan Desain Motif Dengan Teknik Celup Ikat (Tie Dye Technique) Dalam Upaya Meningkatkan Keterampilan Dan Kreatifitas - Endang Tjahjaningsih; Dewi Handayani Utari Ningsih RS; Achmad Badjuri; Alya Takwarina Cahyani (IKRA-ITH ABDIMAS, 2023)
Batik tie dye is part of technique in batik making. Tie dye technique is the easiest to do and develop, although this technique is easy and can be developed, not many people or batik craftsmen have done it and know it. So far, Dharma Wanita women routinely hold activities filled with skills and additional knowledge that can support the ability of human resources in accordance with the goals of Dharma Wanita. The provision of training in tie dye techniques is one of the means of expertise that can be provided so that mothers can explore one of the treasures of batik techniques in the archipelago. The activity of making batik motifs using tie dye technique was attended by Dharma Wanita women from the Public Housing and Settlement Areas of Central Java Province which showed that Dharma Wanita women were able to follow and produce batik motifs from the tie dye technique.